Eco-friendly Techniques for managing white grubs in Uttarakhand hills - Singh, M. P.; Singh, A. K.; Bisht, R. S. (Indian Farming, 2016)
White grubs are the pest of economic importance. Six major species of white grubs namely Holotrichia longipennis Blanch., H. seticollis Mosser, Anomala dimidiata (Hope), A. leneatopennis Blanch., Brahmina coriacea (Hope) and Xylotrypes gideon L. are responsible for major constraint in production of almost all the kharif crops ,vegetables and spices grown under rain-fed farming situation of Uttarakand hills. Both grubs and beetles are polyphagous and univoltine in nature. No single control measure is found effective for their management. Hence, integration of various eco-friendly control measures is only option for their effective management.